PERGESERAN POLITIK HUKUM KOPERASI DALAM UU RI NO. 25 TAHUN 1992 DAN UU RI NO. 17 TAHUN 2012 SERTA PUTUSAN MAHKAMAH KONSTITUSI NO. 28/PUU RI -XI/2013 - Tri Budiyono; Christina Maya Indah S (Masalah-Masalah Hukum, 2015)
This research revealed the shift of political  law as a result  of  implementation  Act of Republic of Indonesia   No.17 of 2012 that reposition Act of Republic of Indonesia No.25of 1992. The implementation of Act of Republic of Indonesia No.17 of 2012 leaved crusial problem because of the lack of values ethic of cooperative. The crucial  problems in Act of  Republic of Indonesia No.17of 2012 related with the reduce of cooperative concept by  limited   as a legal entity. Beside that, the capital aspect   has potential to reduce the value of cooperative, the appointment of cooperative management of non members, and the power of supervisory board of cooperatice, and the distribution of  surplus operating results . The constitutional court with erga omnes character   canceled act of Republic of Indonesia No.17 of  2012 and  maked  transtitional to  re implement Act of Republic of Indonesia No 25 of 1992 as a focus in this research.